(untitled) (Mustansiria Dental Journal, 2018)
The ability of tooth – colored restorative material to resist stain is important because discoloration of it may result in patient dissatisfaction and additional time and expense for replacement. However, the effect of different staining agents on the color difference of resin composite restorative materials has not been completely clarified. The aim of this study was to evaluate the stainability of composan ceram resin composite upon exposure to different drinks. Forty – two disk shaped specimens (10X2mm) were prepared from composan ceram using polytetraflouroethylen mold. The specimens were divided into six groups (n=7) and stored for 7 days at 37Cْ in different types of solutions (distilled water, coffee, coffee with sugar, coffee with sugar and artificial creamer, tea, tea with sugar). Color of all the specimens was measured before and after exposure with spectrophotometer using CIE L* a* b* relative and color changes (E) were then calculated. The data were analyzed with one – way analysis of variance (ANOVA) and LSD test. There was a highly significant difference when comparing the storage agents. Coffee solution produced the most severs stain and it stained composite more than tea. When tea and coffee groups with and without sugar were compared, both groups without sugar demonstrated a higher color difference than with sugar. Coffee stained composite more than tea and the absence of sugar in coffee and tea increased color difference compared to coffee or tea with sugar.